Taxonomic revision of the water scavenger beetle genus Sternolophus Solier, 1834 (Coleoptera: Hydrophilidae) - Nasserzadeh, Hiva; Komarek, Albrecht (Zootaxa, 2017)
The Old World water scavenger beetle genus Sternolophus Solier is revised. Six new species are described: Sternolophus acutipenis sp. n., S. insulanus sp. n., S. jaechi sp. n., S. mandelai sp. n., S. prominolobus sp. n. and S. solitarius sp. n. Three taxa are reinstated as valid species: Sternolophus angustatus (Boheman), S. elongatus Schaufuss and S. mundus (Boheman). The subgenera within the genus are rejected and Neosternolophus Zaitzev syn. n. is synonymized with Sternolophus s. str. Lectotypes are designated for Hydrophilus angolensis Erichson, H. angustatus, H. rufipes Fabricius, Sternolophus brachyacanthus Régimbart, S. comoriensis Fairmaire, S. elongatus, S. frater Schaufuss, and S. rufipes var. foveoliceps Kolbe. On the basis of similar morphological characters, two species-groups are proposed for some of the species within the genus: The angolensis group including S. angolensis, S. inconspicuus (Nietner), S. mundus, and S. solitarius, and the solieri group including S. angustatus, S. elongatus, S. mandelai, S. rufipes Fabricius, and S. solieri Castelnau. Sternolophus unicolor (Castelnau) is considered a nomen dubium. Male genitalia and other diagnostic morphological characters are illustrated, and distribution maps are presented for all 17 species.